pH-triggered charge-reversal and redox-sensitive drug release polymer micelles co-deliver doxorubicin and triptolide for prostate tumor therapy - Xu C (Dove Medical Press, 2018)
Chen Xu,1,* Ri-jin Song,2,* Pei Lu,2,* Jian-chun Chen,1 Yong-qiang Zhou,1 Gang Shen,1 Min-jun Jiang,1 Wei Zhang2 1Department of Urology, The First People’s Hospital of Wujiang City, Suzhou, China; 2Department of Urology, The First Affiliated Hospital of Nanjing Medical University, Nanjing, China *These authors contributed equally to this work Aim: To significantly promote cancer cell uptake and to achieve combination therapy and on-demand drug release, a pH-triggered charge-switchable and redox-responsive drug-release nanovehicle was developed in this study. Materials and methods: The nanocarrier was constructed by conjugating 3,3'-dithiodipropionic acid-modified doxorubicin (DTPA-DOX) and 2,3-dimethylmaleic anhydride (DMA) to the side amino groups of poly(ethylene glycol)-b-poly(L-lysine) (PEG-b-PLL) and by encapsulating triptolide (TRI) into the hydrophobic core. The surface charge of the obtained nanocarriers (DA-ss-DT) can change from negative to positive in response to tumor extracellular acidity pH, and the nanocarriers capably release two drugs in response to intracellular high glutathione (GSH) environment. Results: Compared to the control group, the in vitro cellular uptake of DA-ss-DT by human prostate cancer PC-3 cells was significantly promoted in slightly acidic conditions, and the drug could be rapidly released in the high concentration of GSH conditions. The in vitro and in vivo antitumor experiments exhibited that the DA-ss-DT nanoparticles have a great antitumor effect in comparison to the control group. Conclusion: These findings demonstrated that the DA-ss-DT nanoparticles supply a useful strategy for promoting cellular uptake and synergetic anticancer therapy. Keywords: combination therapy, charge reversal, redox-responsive, pH-responsive